Validation of plasma microRNAs as biomarkers in sepsis associated acute kidney injury upon first clinical presentation reveals limited diagnostic and prognostic performance - Tamar J. van der Aart; Matthijs Luxen; Jacqueline Koeze; Marco van Londen; Matthias Hackl; Jan C. ter Maaten; Matijs van Meurs; Hjalmar R. Bouma (PLoS ONE, 2025)
Background Sepsis is a life-threatening response to an infection, often complicated by sepsis-associated acute kidney injury (SA-AKI). Early recognition of SA-AKI is critical but challenged by the limited sensitivity of existing diagnostic markers. MicroRNAs (miRNAs), which regulate key SA-AKI pathways, have shown diagnostic promise, yet their clinical utility in early SA-AKI recognition remains unexplored. Moreover, validation in relevant clinical settings and populations remains limited. Therefore, this study aims to explore the potential of miRNAs for early recognition of SA-AKI at emergency department (ED) presentation, and explore the generalizability of findings by including a cohort of intensive care urine (ICU) patients with more advanced disease. Methods We conducted a post-hoc analysis of prospectively collected data from patients admitted to the ED and ICU. We performed a thorough literature review to select twelve miRNAs, previously implicated in kidney injury and sepsis or SA-AKI. MiRNAs were extracted from plasma and quantified using qPCR with and normalization to the global mean. We measured plasma levels of selected miRNAs upon ED arrival in 193 acutely ill patients (no infection, n = 65; sepsis, n = 67; SA-AKI, n = 61), and 47 critically ill patients (sepsis, n = 18; SA-AKI, n = 29). Statistical analyses included logistic and Cox regression adjusted for clinical variables, with correlations assessed between miRNA levels and disease severity markers. Diagnostic performance was evaluated using receiver operating characteristic (ROC) curve analysis. Results MiR-21-5p (OR 2.28, 95% CI [1.40–3.73]; p < 0.01) and miR-16-5p (OR 0.74, 95% CI [0.59–0.93]; p = 0.01) levels were associated with SA-AKI at ED presentation. Furthermore, miR-21-5p was independently associated with 30-day mortality after adjusting for age, illness severity, and comorbidities (adjusted OR 2.30, 95% CI [1.38–3.86]; p < 0.01). Similarly, in the ICU cohort with more advanced sepsis, miR-21-5p was associated with SA-AKI (OR 3.48, 95% CI [1.27–9.53]; P = 0.02), achieving an AUC of 0.74 (95% CI [0.58–0.89]), although it was not associated with 30-day mortality in this cohort. Conclusion We selected twelve miRNAs through literature review associated with kidney injury, sepsis or SA-AKI. Of these, only miR-21-5p was associated with SA-AKI and predicted 30-day mortality upon ED admission. This analysis effectively serves as a negative validation for most literature-derived miRNAs, challenging their clinical applicability identification of SA-AKI both at early presentation and in more advanced stages. Trial registration This study is embedded in the Acutelines data-biobank (www.acutelines.nl), registered in Clinicaltrials.gov (NCT04615065, November 3rd 2020) and the The Biobank Intensive Care Groningen registered in Clinicaltrials.gov (NCT04502511, August 6th 2020).